The Effect of Virtual Reality-Based Therapy on Improving Upper Limb Functions in Individuals With Stroke: A Randomized Control Trial - El-Kafy, Ehab Mohamed Abd; Alshehri, Mansour Abdullah; El-Fiky, Amir Abdel-Raouf; Guermazi, Mohamad Abdelhamid (Frontiers in Aging Neuroscience, 2021)
Background: Stroke is a common cause of motor disability. The recovery of upper limb after stroke is poor, with few stroke survivors regaining some functional use of the affected upper limb. This is further complicated by the fact that the prolonged rehabilitation is accompanied by multiple challenges in using and identifying meaningful and motivated treatment tasks that may be adapted and graded to facilitate the rehabilitation program. Virtual reality-based therapy is one of the most innovative approaches in rehabilitation technology and virtual reality systems can provide enhanced feedback to promote motor learning in individuals with neurological or musculoskeletal diseases. Purpose: This study investigated the effect of virtual reality-based therapy on improving upper limb functions in individuals with chronic stroke. Methods: Forty Saudi individuals with chronic stroke (6–24 months following stroke incidence) and degree of spasticity ranged between 1, 1+ and 2 according to Modified Ashworth Scale were included in this study. Participants were randomly assigned into two groups, experimental and control, with the experimental group undertaking a conventional one-hour functional training program, followed by another hour of virtual reality-based therapy using Armeo Spring equipment and the control group received two hours of a conventional functional training program. The treatment program was conducted three times per week for three successive months. The change in the scores of Action Research Arm Test (ARAT), Wolf Motor Function Test (WMFT), WMFT-Time (time required to complete the test) and Hand Grip Strength (HGS) were recorded at baseline and after completion of the treatment. Results: Both groups showed significant differences (all, P < 0.05) in all measured variables after three months of the treatment. Individuals with stoke in the experimental group (all, P < 0.01) had a better improvement in ARAT, WMFT and WMFT-Time scores after completion of the treatment compared to the control group. No significant difference in HGS scores was detected between groups after completion of the treatment. Conclusions: The use of combined treatment of virtual reality-based therapy and conventional functional training program is more effective for improving upper limb functions in individuals with chronic stroke than the use of the conventional program alone.